Gold and Carbon-Based Nano-theranostics: An Overview on the Developments and Applications for Cancer Phototherapy - Ashay Manisha Shailendrakumar; Vamshi Krishna Tippavajhala (Tabriz University of Medical Sciences, 2022)
Nano-theranostics (NTs) are versatile nanomaterials, explored in the current scenario of cancer therapy. A nano-theranostic material alone can diagnose and generate a therapeutic effect. Various materials have been explored for their NT action like gold and carbon-based material. The photon-based cancer theranostics has grabbed the attention of researchers due to their localized and trigger activated effect. NTs have shown a promising result in pre-clinical and clinical studies. The current review illustrates the meticulous efforts conducted by researchers across the globe to innovate and explore the photon-based cancer NT platforms of gold and carbon with their application in cancer therapy.